The Implementation of Knowledge Management in Conservation Construction Firms: An Empirical Study on Organisational Readiness - Abdullah, Shardy; Abdul Razak, Arman; Ismail, Suriatini (International Journal of Sustainable Construction Engineering and Technology, 2021)
The difficulty and complexity of implementing conservation projects on Malaysian heritage buildings have led to construction firms to be more innovative in integrating the implementation process with other concepts from various different disciplines and fields. In this study, the need to implement knowledge management among the conservation construction firms is seen to be a significant aspect, particularly to enable these firms to optimize the available knowledge among the workers in order to remain competitive. However, studies related to the level of exposure as well as discussions of knowledge management implementation in conservation construction firms in Malaysia are extremely limited. The purpose of this study is to determine the level of readiness among conservation construction firms towards the implementation of knowledge management in their organisations as well as to evaluate the relationship between organisational readiness with the readiness components. The data needed for this study was collected through a survey, where a specific questionnaire was designed and distributed to selected employees working in conservation construction firms. The main finding of this study shows that the level of readiness among most of these conservation construction firms is relatively good where it has been proven that these firms are capable of realizing the implementation of knowledge management in their respective organizations. The study findings also reveal that there is a strong relationship between organisational readiness with all readiness components that had been tested within this study.